A new electricity market design for power systems with large share of hydro: improving flexibility and ensuring efficiency and security in the Brazilian case - Felipe Alves Calabria (2015)
This paper discusses some problems related with the current Brazilian electricity market, brings out some dilemmas that should be examined in order to implement a more market oriented approach, and proposes a new market design to overcome these issues. The proposed market design is based on the concept of energy right accounts as virtual reservoirs and aims at enhancing the flexibility to enable market participants to comply with their contracts, while still ensuring the efficient use of the energy resources and maintaining the current security supply level. In addition, in order to simulate the behavior of the market participants in this new framework, an Agent-Based Model - ABM where agents use reinforcement Q-Learning is developed for the study case. The results show that this new market design is suitable to be applied to hydrothermal systems having a large share of hydros.